Effectiveness Of Retro Walking Treadmill Training On Pain And Disability In Knee Osteoarthritis: A Randomized Controlled Trail - HARDIK ANADKAT,; AJITH S,; DHANESH KUMAR K U,; AJITH S, (International Journal of Pharma and Bio Sciences, 2015)
Osteoarthritis (OA) is the second most common rheumatological problem and is most frequent joint disease with a prevalence of 22% to 39% in India. Standard physical therapy for OA usually consists of strengthening exercises, ROM exercises, manual therapy and stretching and aerobic exercises. The purpose of this study was to determine the effect of Retro walking Treadmill Training, in addition to conventional exercises in knee OA patients. This 3 week study was conducted on 40 patients with knee OA who were randomized into 2 groups. There was statistically significant improvements were observed within the groups with respect to VAS and WOMAC. When the comparison made between groups the difference was statistically significant (p<.05) for both the parameters. The study concluded that the combination of retro walking treadmill training and conventional exercises is more effective than conventional exercises alone in knee OA patients to reduce pain and disability.